Diabetes mellitus in major head and neck cancer surgery: Systematic review and meta‐analysis. Issue 10 (11th July 2020) - Caputo, Mathew P.; Shabani, Sepehr; Mhaskar, Rahul; McMullen, Caitlin; Padhya, Tapan A.; Mifsud, Matthew J.
Abstract: Background: Diabetes mellitus (DM) is a risk factor for surgical complications and a common comorbidity in the setting of head and neck (H&N) cancer. Our objective was to determine if DM is associated with increased rates of H&N cancer surgery complications. Methods: We conducted a search of Pubmed, Embase, and the national clinical trials database focusing on H&N cancer surgery or free flap reconstruction and diabetes. Two reviewers screened studies by title/abstract and then full text. We then collected data using a pre‐made template. Meta‐analysis was performed using Revman 5.3. Results: Of the 272 results from Pubmed and 559 from Embase, we selected 16 studies for inclusion. Meta‐analysis revealed DM was associated with increased rates of flap failure (risk ratio [RR] = 1.83 95% confidence interval [CI], 1.18‐2.85; P = .007) and local complications (RR = 1.87 95% CI, 1.24‐2.80; P  < .00001). Conclusion: Although DM is associated with increased risk of flap failure and local H&N cancer surgery complications, further research is required to optimize care in this population.